The Effect of Using an Electronic Teaching Package on (Cognitive & Skill) Self Learning for Service & Receive in Volleyball - Abdelsalam Hussein (My University, 2008)
The aim at this study was to investigate the effect of using electronic teaching package on (cognitive & skill) self-learning for service & receive ball in volleyball, & compare with the traditional method of teaching. The sample consisted of (30) students from (ALMAREF al –AHLEYYAH KINDERGARTEN) divided into: control group (15) that used instructional method and experimental group (15) that used self-learning method using. Results revealed that both methods had appositive effect on learning service & receive ball skills in volleyball. There was significant difference between posts & pre-test, post test scores were higher than pre-test scores: in addition when comparing the two groups in the post test significant differences were appeared in favor of the experimental group. It was recommended that the electronic teaching package should be used on (cognitive & skill) self-learning for service & receive ball skills.